Kinetic modeling of gas phase synthesis of ethyl chloride from ethanol and HCl in fixed bed reactor. (13th March 2016) - Bukhanko, Natalia; Wärnå, Johan; Samikannu, Ajaikumar; Mikkola, Jyri-Pekka
Abstract: Kinetic modeling of gas-phase synthesis of ethyl chloride from ethanol and hydrochloric acid over high porous Al2 O3 and 2 wt% ZnCl2 /Al2 O3 catalysts was studied in a continuous plug flow reactor in the temperature range of 200–325 °C. Two rival kinetic models were proposed that both describe the kinetics well. The kinetic parameters of the reaction were determined and activation energy values for ethyl chloride formation from ethyl alcohol and diethyl ether reactions were calculated. Graphical abstract: Highlights: Gas-phase process of ethyl chloride synthesis from ethanol and HCl over high porous Al2 O3 -based catalysts in a bed-fixed reactor was investigated. Two rival kinetic models for the description of process kinetic were proposed. The values of rate constants, reaction equilibrium constants and activation energy were calculated for both kinetic models.